The Theoretical Description of Sudan Dyes Electrochemical Determination on A Triazolic Derivative - Volodymyr V. Tkach, Marta V. Kushnir , Lyudmyla V. Romaniv , Olga V. Pishak , Sílvio C. de Oliveira (Appl. J. Envir. Eng. Sci., 2023)
The theoretical description of the electrochemical determination of sudan dyes, assisted by novel triazolic derivatives, using a disulfonic organic acid as a binder, has been made. The correspondent mathematical model was analyzed by means of linear stability theory and bifurcation analysis. It was shown that the electroanalytical process is realized more efficiently than in the case of the direct electrochemical reduction in acid media. The oscillatory behavior for this case is possible, but less probable than for direct dye electrochemical reduction
Keywords: hemically modified electrodes, sudan dyes, triazole, electrochemical sensors, stable steady state